Laser bending angle and surface quality with preload at low heating temperature. (April 2021) - Shi, Yongjun; Guo, Yankuo; Wang, Xiaogang; Sun, Rui; Li, Xianfa
Highlights: Large laser thermal bending and high surface quality can be obtained under low-temperature preload. The multiple scanning of low-temperature preload can get larger bending angle and better surface quality. The bending direction of plate can be controlled by preload. Abstract: Laser thermal bending under preload is a new research direction in the field of laser thermal bending. Under the background of low cost and high efficiency pursued by the state and enterprises, this paper adopts the form of low heating temperature to study laser thermal bending under preload. In this paper, the bending angle and surface quality under without load, low-temperature preload and high-temperature preload are compared by experiment and simulation. In addition, the process and forming mechanism of low-temperature preload are discussed by simulation. The results show that the bending angle can be increased by 39 times by low-temperature preload compared with the without load. Low-temperature preload achieves a high surface quality compared to high-temperature preload. The preload plays a dominant role in bending direction at low-temperature preload, and the bending direction of plate can be controlled by the preload. In addition, the multiple scanning of low-temperature preload not only gets better surface quality, but also gets a larger bending angle. Large preload and free end distance can improve the bending angle. The deformation mechanism shows that the addition of preload can effectively increase the flow stress value and deformation area, which will form a larger bending angle.